2010
DOI: 10.1111/j.1532-5415.2010.02724.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Is Associated with Greater Incident Dehydroepiandrosterone Sulfate Decline in the Oldest Old: The Cardiovascular Health Study All Stars Study

Abstract: OBJECTIVES-To describe cross-sectional and longitudinal associations with dehydroepiandrosterone sulfate (DHEAS) and change in DHEAS with age. DESIGN-Longitudinal cohort study.SETTING-Pittsburgh, Pennsylvania. PARTICIPANTS-CardiovascularHealth Study All Stars study participants assessed in 2005/06 (N =989, mean age 85.2, 63.5% women, 16.5% African American).Address correspondence to Jason Sanders, 4614 Fifth Ave, Apt 217, Pittsburgh, PA 15213. sanders.jason@medstudent.pitt.edu. The work from which this manuscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Besides the higher insulin resistance of AH-PCOS women, the intriguing relationship found between the lipid profiles and AH of our patients may support the proposed protective effect of DHEAS against cardiovascular diseases (40)(41)(42), especially in obese patients. Although we observed decreased HDL cholesterol levels in nonobese AH-PCOS women, there was also a near significant decrease in TC concentrations, explaining why the TC to HDL cholesterol ratio-the most effective lipid screening method to estimate cardiovascular risk (43)-remained unchanged.…”
Section: Figure 2 Continuedsupporting
confidence: 51%
“…Besides the higher insulin resistance of AH-PCOS women, the intriguing relationship found between the lipid profiles and AH of our patients may support the proposed protective effect of DHEAS against cardiovascular diseases (40)(41)(42), especially in obese patients. Although we observed decreased HDL cholesterol levels in nonobese AH-PCOS women, there was also a near significant decrease in TC concentrations, explaining why the TC to HDL cholesterol ratio-the most effective lipid screening method to estimate cardiovascular risk (43)-remained unchanged.…”
Section: Figure 2 Continuedsupporting
confidence: 51%
“…The Cardiovascular Health Study (CHS) All Stars Study conducted an examination in 2005–06 of CHS participants aged 77 years and older that included measure of cognitive and physical function [33]. Several publications from CHS All Stars are relevant [34,35,36,37,38,39,40] but none specifically addressed the predictors of reaching older age in good physical, cognitive, and psychological health.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, evaluation of diurnal regulation of DHEAS across development may also be an important risk factor for disease. Prior studies of DHEAS across the lifespan indicated that lifetime trajectories of DHEAS concentrations, rather than baseline DHEAS concentrations alone were associated with higher mortality in older adults (Cappola, A. R. et al, 2009) as well as cardiovascular disease (Sanders, J. L. et al, 2010). Consequently, these results encourage the characterization diurnal DHEAS profiles and the estimation of genetic and environmental contributions to profiles across the lifespan.…”
Section: Discussionmentioning
confidence: 99%